Metabolic rejuvenation upgrades circulatory functions of red blood cells stored under blood bank conditions. Issue 3 (31st December 2020) - Marin, Mickaël; Roussel, Camille; Dussiot, Michael; Ndour, Papa A.; Hermine, Olivier; Colin, Yves; Gray, Alan; Landrigan, Matt; Le Van Kim, Caroline; Buffet, Pierre A.; Amireault, Pascal
Abstract: Background: Red blood cells (RBC) change upon hypothermic conservation, and storage for 6 weeks is associated with the short‐term clearance of 15% to 20% of transfused RBCs. Metabolic rejuvenation applied to RBCs before transfusion replenishes energetic sources and reverses most storage‐related alterations, but how it impacts RBC circulatory functions has not been fully elucidated. Study Design and Methods: Six RBC units stored under blood bank conditions were analyzed weekly for 6 weeks and rejuvenated on Day 42 with an adenine‐inosine–rich solution. Impact of storage and rejuvenation on adenosine triphosphate (ATP) levels, morphology, accumulation of storage‐induced microerythrocytes (SMEs), elongation under an osmotic gradient (by LORRCA), hemolysis, and phosphatidylserine (PS) exposure was evaluated. The impact of rejuvenation on filterability and adhesive properties of stored RBCs was also assessed. Results: Rejuvenation of RBCs restored intracellular ATP to almost normal levels and decreased the PS exposure from 2.78% to 0.41%. Upon rejuvenation, the proportion of SME dropped from 28.2% to 9.5%, while the proportion of normal‐shaped RBCs (discocytes and echinocytes 1) increased from 47.7% to 67.1%. In LORCCA experiments, rejuvenation did not modify the capacity of RBCs to elongate and induced a reduction in cell volume. In functional tests, rejuvenation increased RBC filterability in a biomimetic splenic filter (+16%) and prevented their adhesion to endothelial cells (−87%). Conclusion: Rejuvenation reduces the proportion of morphologically altered and adhesive RBCs that accumulate during storage. Along with the improvement in their filterability, these data show that rejuvenation improves RBC properties related to their capacity to persist in circulation after transfusion.